Inside the castle : law and the family in 20th century America - Grossman, Joanna L.; Friedman, Lawrence M. (Lawrence Meir), 1930- (Princeton : Princeton University Press, 2017)
This title provides a comprehensive social history of 20th-century family law in the United States. Joanna Grossman and Lawrence Friedman show how vast, oceanic changes in society have reshaped and reconstituted the American family.
Previously issued in print: 2011.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 5, 2017).
Keywords: Domestic relations -- United States -- History -- 20th century; Marriage law -- United States -- History -- 20th century; Parent and child (Law) -- United States -- History -- 20th century; Children -- Legal status, laws, etc. -- United States -- History -- 20th century; United States -- Social conditions -- 20th century; Law; United States of America, USA; Laws of specific jurisdictions & specific areas of law; Family law